Batteries and Fuel Cells with Convective Mobile Electrolyte. (25th October 2017) - Fischel, Halbert; Lubin, Philip; Clark, Brian
Abstract : Novel cost effective mobile electrolyte secondary battery and fuel cell architecture is proposed using tested properties of advanced materials. Otherwise high functioning historic fuel cell issues are potentially solved. Electrolyte circulation in BOP is simplified whereby multiple unit-cells connected in series for high voltage no longer discharge along fluid pathways. Active cores are compact, having high energy to weight and volume ratio. Forced convective permeability exceeds 20 Darcy at 1 cp viscosity for fluid velocity above 1 cm/sec. Direct-oxidation of suitable hydrocarbon fuels is virtually complete within the anode and convection of concentrated cation within the cathode accelerates ORR to improve O2 breathing in LIB and other faradaic and catalytic chemistries. These benefits are possible only when ultralow resistance electrodes, comprising porous cohesive nonwoven CNT membranes as a substrate, are uniquely attached to metal current collectors more fully described in a supplement following the main article.